Sociological Approach to the Role of the Family in Religious Values Internalisation - Gunawan; Rifai, Muhammad; Maulida Masyitoh; Asni Sari, Kurnia; Maulidya, Ade (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
Religion is one of the important aspects of human life that can affect a person, be it the way they think, act, and interact with the surrounding world. Religious education begins with the education obtained in a family. Therefore, this research aims to see how a family, which is the smallest unit in society, provides religious education for children. One of the novelties of this research is that the author explores the research findings more broadly and deeply, and gives emphasis to the socialisation process in the family. This research employed the literature study research method. This method was chosen. It can answer the questions posed more comprehensively because it refers to several scientific quantities that have been published previously. The theory used to analyse the findings is Functional Structural Theory. This theory was chosen because it is relevant to explain how a structure carries out its functions and roles, to be able to achieve a goal. The results showed that a family has a big responsibility in instilling religious values in a child. This responsibility is carried out in the form of socialisation and interaction between family members. How the family transforms religious values for each child is one of the fundamental things that will affect a child's religious understanding. The family, as the smallest structure in society, has a great function and role in shaping a child's character, including the cultivation of religious values.